1989
DOI: 10.1007/bf00153501
|View full text |Cite
|
Sign up to set email alerts
|

Intra-ocular light scatter in pseudophakia

Abstract: In 22 patients (23 eyes), who had undergone an uncomplicated cataract extraction with implantation of a posterior chamber lens in otherwise normal eyes 11 to 44 weeks previously, the intra-ocular light scatter was measured with an IOI stray light meter. All the eyes examined had little or no after-cataract. A regression curve for stray light values in normal eyes as function of age was used as reference. The measurements show that the intra-ocular light scatter in pseudophakic eyes with little or no after-cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 5 publications
(9 reference statements)
2
11
0
1
Order By: Relevance
“…However, there is often a discrepancy between these 2 guiding principles and the degree of the patient's visual impairment. [1][2][3][4][5][6] Many patients with PCO have disability glare, which is defined as a reduction in visual capacity resulting from a nearby glare source and is the result of forward intraocular light scatter. The international standards committee Commission International de l'Eclairage quantifies disability glare as straylight.…”
mentioning
confidence: 99%
“…However, there is often a discrepancy between these 2 guiding principles and the degree of the patient's visual impairment. [1][2][3][4][5][6] Many patients with PCO have disability glare, which is defined as a reduction in visual capacity resulting from a nearby glare source and is the result of forward intraocular light scatter. The international standards committee Commission International de l'Eclairage quantifies disability glare as straylight.…”
mentioning
confidence: 99%
“…This may cause the optical condition of the eye to be less than perfect, even in patients without after-cataract. In fact it has been reported that in patients with IOLs as a rule straylight is increased [7].…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48][49] reported negative dysphotopsia in 15.2% on the first postoperative day, 3.2% at 1 year, and 2.4% at 2 to 3 years. In Figure 15, we see that as long as the nasal capsule remains clear, there is no light scattered into the shadow.…”
Section: Natural Course and Treatmentsmentioning
confidence: 95%